1988
DOI: 10.1037/0278-6133.7.2.137
|View full text |Cite
|
Sign up to set email alerts
|

The borderline hypertensive rat: A model for studying the mechanisms of environmentally induced hypertension.

Abstract: The borderline hypertensive rat (BHR) is a first-generation cross between the spontaneously hypertensive rat and the normotensive Wistar-Kyoto rat. The BHR develops frank hypertension when chronically stressed or when fed a high-sodium diet. Stress-induced hypertension can be blocked by exercise. The role of the central nervous system and kidney in hypertension development in this model is discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
14
0

Year Published

1991
1991
2018
2018

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(15 citation statements)
references
References 16 publications
1
14
0
Order By: Relevance
“…Exposure to stress has been found to accelerate hypertension development in SHR (28,29) and several authors have noted the relationship between enhanced cardiovascular activation and enhanced risk in humans (4,5). The mechanism for this relationship is still unclear, although it has been suggested that increased cardiovascular activation is a contributor to hypertension development (5).…”
Section: Discussionmentioning
confidence: 98%
“…Exposure to stress has been found to accelerate hypertension development in SHR (28,29) and several authors have noted the relationship between enhanced cardiovascular activation and enhanced risk in humans (4,5). The mechanism for this relationship is still unclear, although it has been suggested that increased cardiovascular activation is a contributor to hypertension development (5).…”
Section: Discussionmentioning
confidence: 98%
“…Previous studies have shown that a genetic predisposition to hypertension is necessary for the development of this pathology in both humans and rats (Lawler and Cox, 1985;Henry et al, 1986;Lawler et al, 1988). An increased sympathetic drive and exaggerated response of the HPA axis may account, in part, for stressinduced hypertension.…”
Section: Figmentioning
confidence: 99%
“…The BHR represents the F 1 offspring between SHR and Wistar-Kyoto (WKY) rats, being very sensitive to external inputs, while still maintaining the nonnotensive phenotype of their WKY parents (Lawler and Cox, 1985). When subjected to chronic intermittent stress (or a diet rich in NaCl), BHRs have been shown to develop a sustainable hypertension (Lawler et al, 1981(Lawler et al, , 1988Fisher and Tucker, 1991;Mansi and Drolet, 1997); otherwise, if left unstressed, they remain in the high normotensive range for arterial pressure (Lawler et al, 1988; Mansi and Drolet, Received November 12, 1997; revised manuscript received November 25, 1997; accepted November 26, 1997. Address correspondence and reprint requests to Dr. G. Drolet at Centre Hospitalier Universitaire de Québec, Pavillon CHUL, Unité de Neuroscience, 2705 Boulevard Laurier, Ste-Foy, Québec,Canada, G1V 4G2.…”
Section: Introductionmentioning
confidence: 99%
“…Experiments were performed in BHR and Wistar–Kyoto rats (WKY; control strain). BHR are the first generation offspring of spontaneously hypertensive rats (SHR) and WKY; previously only the male offspring have been studied (Lawler et al . 1988).…”
mentioning
confidence: 99%